THE POLICY OF CURRICULUM DEVELOPMENT IN EDUCATION MANAGEMENT FOR CADET OF INDONESIAN NAVAL ACADEMY - Wahrobun Wahrobun; H Rufi'i; Muhammad Muhyi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Graduates of the Surabaya Naval Academy in the next 25 years will occupy the leadership of the Navy's organization with all its complexity and problems. So that the nurturing method implemented at the Indonesian Navy Academy will greatly affect the results of the cadets. The aim of this research is to develop a product for developing cadet Caregiving curriculum based on curriculum developed theories. The method used in this research is descriptive qualitative by carrying out open and closed questionnaires and data triangulation validation. The results showed that the validation of the experts obtained results; 88% design, 90% content, 88% linguistics and 94% material presentation. While the results of field trials: individual test 91.75%, small group test 93.55% and large group test 89.25%. The average results of expert validation and field tests were 90.65%. So that the factors developed during the development of the AAL cadet parenting curriculum are design aspects including feasible categories, content aspects including feasible categories, linguistic aspects including feasible categories and aspects of material presentation including feasible categories so that the AAL cadet parenting curriculum is feasible to use. Keywords: Curriculum development, Parenting Curriculum, Military Academy Youth Navy.